Analisis Faktor-Faktor Perilaku Seksual pada Remaja di SMAN 2 Kota Tarakan: Implikasi Penyakit Menular Seksual - Irma Irawan; Vinny Alvionita; Rusmiati; Tanti Tri Lestary; Rizky Vaira (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Risky sexual behavior of adolescents, such as premarital sexual intercouse without using contraceptives, has the potential of to increase sexually transmitter diseases (STDs). Some factors that contribute to this behavior include the low level of knowledge of adolescents, the role of parents and peers, and the influence of social media. Premilinary studies conducted in several school in Tarakan City showed that adolescents’ knowledge abot adolescent sexual behavior that has an impact on STDs was still limited, accompanied by the discovery of cases of pregnancy out of marriage. This study aimed to analyzed the factors of adolescent sexual behavior at SMAN 2 Tarakan City. This study employed a cross-sectional design to identify the relationship between independent variabels (level of knowledge, role of parents, peers, and social media) and the dependent variable (adolescent sexual behavior). The research was conducted in April 2025 and involved 94 respondents using a systematic random sampling technique. The instrument use was a questionnaire that had been tested for validity and reliability. Data analysis was conducted using the chi-square test and alternative cell grouping. The result of the study indicated that there was no significant relationship between the level of knowledge and adolescent sexual behavior (p=0,222). However, there was a significant relationship between the role of parents (p<0,001), peers (p<0,001), and social media (p<0,001) on adolescent sexual behavior. It is hoped that it can provide on overview to the community regarding the importance of knowledge, the role of parents, the influence of peers, and the use of social media that affect the sexual behavior of adolescents who are at risk of sexually transmitted diseases